Vaccine Formulation for Infectious Diseases and Adjuvant Mechanisms of Action - Heather L. Wilson; Azita Haddadi; George K. Mutwiri (Vaccines, 2021)
The ultimate goal for vaccination is the generation of a safe and effective immune response that protects against diseases [...]